Occupational and environmental exposures of overhead distribution lineworkers and environmental impacts of creosote: a cross-sectional study - Sofia Poursanidou; Cavoura, Olga (International Journal of Occupational Safety and Health, 2026)
Introduction: Workers in overhead electrical distribution networks (OEDNs) face numerous physicochemical hazards. In Greece, wooden poles (WPs) used in OEDNs are typically treated with creosote, a complex mixture containing polycyclic aromatic hydrocarbons (PAHs), heteroaromatic compounds and tar acids/bases. Creosote is a probable human carcinogen and a skin and eye irritant and can result in environmental contamination from creosote “bleeding”. Methods: A cross-sectional study of the health effects in OEDNs in Northern Greece was conducted between January and September 2024. Fifty-six employees (70% response) completed a structured questionnaire covering demographic data, opinions and attitudes towards personal protective equipment (PPE), and the potential impact on their health and the environment arising from creosote in WPs. Ethics approval was received from the University of West Attica Ethics Committee (Ref. No. 4608, 24 Jan 2024). Results: Frequent contact with creosote-treated poles was reported by 66.1% of participants. While climbing newly creosote-treated poles, workers reported skin burns (46.4%), eye irritation (32.1%), and dermatitis (25.0%). Symptoms were described as more intense during the summer. Of the sample group, 66.1% recognized creosote-related health hazards, 42.9% were aware of the potential for soil contamination, and 30.4% for water contamination. Conclusion: Based on the study findings, creosote remains a tangible occupational and environmental hazard for line workers, especially when climbing newly creosote-treated poles. Environmental contamination from treated WPs was mainly localized in the surrounding soil, driven by creosote seepage and PAHs leaching. The phasing out of creosote, revising safety standards, and strengthening worker training are priorities for prevention.